Early literacy and child wellbeing: Exploring the efficacy of a home-based literacy intervention on children's foundational literacy skills. (June 2022) - Derby, Melissa; Macfarlane, Angus; Gillon, Gail
This paper reports on findings from a doctoral study that explored the efficacy of a home-based literacy intervention in advancing preschool children's foundational literacy skills. Two key cognitive skills critical for early literacy success were examined in particular, those being phonological awareness, and elements of oral language, including vocabulary knowledge, which is the specific skill discussed in this paper. The intervention consisted of two main areas of focus – one, named Rich Reading and Reminiscing (RRR), concentrated on stimulating children's oral language skills, and the other, called Stimulating Sound Sensitivity (SSS), aimed to generate shifts in children's phonological awareness abilities. Data sets were gathered with eight children and their families over a twelve-week period, which corresponded with the duration of the intervention. A final set of data was collected six months after the intervention ceased. The study employed a crossover design, where four children and their families participated in the RRR component of the intervention, which ran for six weeks, followed by the SSS portion of the intervention. The remaining four children participated in the same parts of the intervention but in reverse order of delivery. The crossover approach established a control in the study, and allowed the effects of each part of the intervention on the children's early literacy skills to be more clearly revealed. This paper reports on two children – one from each cohort – whose results are evidence of the efficacy of the intervention in advancing key aspects of children's foundational literacy skills. Key Findings: The children who participated in the RRR component of the intervention first showed improvements in vocabulary knowledge mid-intervention. Conversely, the children who participated in the SSS component first made gains in their phonological awareness skills before the other cohort of children did. These findings have implications for early childhood educators and families concerning the strategies adopted by these stakeholders which aim to foster strong cognitive skills critical for literacy success.